PENDAMPINGAN KELAS IBU HAMIL MELALUI LAYANAN BIMBINGAN DAN KONSELING ISLAM UNTUK MENGURANGI KECEMASAN PROSES PERSALINAN - Widayat Mintarsih (Sawwa: Jurnal Studi Gender, 2017)
Physical and psychological changes cause problems for pregnant women such as: lack of confidence, dependence on partner, even worried and anxious. To reduce the anxiety, women need assistance through the process of Islamic guidance and counseling services. It is an effort to help individual overcome such deviations of religious nature as well as accept his role as khalifah that create good relationship with God, man and the universe. The lack of Islamic guidance and counseling services provided by health workers from hospital or village midwives brings the enthusiasm to get Islamic counseling especially for pregnant women, their families, integrated services post (Posyandu) cadres, and society in general to be able to overcome their problems. Method of PAR (Participatory Action Research) through awarenes actions towards their condition was used in this research. Assistance through Islamic counseling services meets the needs of pregnant women to reduce anxiety in order to maintain physiological, psychological, and spiritual health. In addition, this kind of services gives an increasing knowledge and insight cognitively, affectively, and psychomotor for pregnant women. Internal cares both medically and through Islamic guidance and counseling services to reduce anxiety for pregnant women is done by themselves, their husband and family while external assistance can be done by the cadres of integrated services post, midwives, and community leaders. An increase and decrease in anxiety were measured by Hamilton Rating Scale for Anxiety’s theory (HRS-A) in Hawari. The result analysis showed that there were 11 clients experiencing decreased anxiety after receiving the Islamic counseling services. Before services, it was found a person suffering from slight category of anxiety, in which indicated the range of 14-20. Moreover, it was found 10 people suffering from medium category of anxiety, with total criteria of assessment from range 21-27._________________________________________________________Perubahan fisik dan psikologis menyebabkan problematika bagi ibu hamil, seperti kurang percaya diri, ketergantungan kepada pasangan, bahkan sampai merasa khawatir dan cemas Untuk mengurangi kecemasan dibutuhkan pendampingan melalui proses layanan bimbingan dan konseling Islam. Minimnya layanan bimbingan dan konseling Islam yang diberikan oleh petugas kesehatan dari Puskesmas atau bidan desa menyebabkan antusias warga khususnya ibu hamil menginginkan diadakannya layanan bimbingan dan konseling Islam khususnya ibu hamil, keluarga ibu hamil, kader Posyandu, dan masyarakat pada umumnya agar mampu mengatasi masalah yang mereka alami. Metode Pengabdian yang dilakukan berbasis PAR (Participatory Action Research) melalui penyadaran tindakan menuju perbaikan kondisi kehidupan mereka. Pendampingan melalui layanan bimbingan dan konseling Islam memenuhi kebutuhan ibu hamil untuk mengurangi kecemasan sehingga bisa menjaga kesehatan fisiologis, psikologis, dan spiritual, serta ada peningkatan pengetahuan dan wawasan dari segi kognitif, afektif, dan psikomotorik. Pendampingan secara medis dan melalui layanan bimbingan dan konseling Islam untuk mengurangi kecemasan internal ibu hamil dilakukan oleh diri sendiri, suami, dan keluarga sedangkan pendampingan eksternal bisa dilakukan oleh kader Posyandu, para bidan, dan tokoh masyarakat. Peningkatan dan penurunan kecemasan didiagnosa menggunakan alat ukur teori Hamilton Rating Scale for Anxiety (HRS-A) dalam Hawari yang menghasilkan analisis bahwa terdapat 11 klien yang mendapatkan layanan bimbingan dan konseling Islam mengalami penurunan kecemasan. Sebelum mendapatkan layanan, terdapat 1 orang mengalami kecemasan kategori ringan dengan kriteria total penilaian dari rentang 14-20 dan kategori kecemasan sedang ada 10 orang dengan kriteria total penilaian dari rentang 21-27.